2012
DOI: 10.1523/jneurosci.0383-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Influences of Opiates and Expectations on Pain

Abstract: Placebo treatments and opiate drugs are thought to have common effects on the opioid system and pain-related brain processes. This has created excitement about the potential for expectations to modulate drug effects themselves. If drug effects differ as a function of belief, this would challenge the assumptions underlying the standard clinical trial. We conducted two studies to directly examine the relationship between expectations and opioid analgesia. We administered the opioid agonist remifentanil to human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
160
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(171 citation statements)
references
References 60 publications
5
160
2
4
Order By: Relevance
“…One approach to investigate additive versus interactive effects of drug and placebo is to adopt a balanced placebo design (Rohsenow and Marlatt, 1981), in which the factors expectancy and drug alternate in a 2 Â 2 factorial manner. Employing just such a design, Atlas et al (2012) observed additive rather than interactive effects in conjunction with the influence of positive expectation on remifentanil analgesia. Their results were substantiated by a complementary fMRI study investigating pain-related responses during the open and hidden administration of varying remifentanil dosages, also allowing inferences about potential interactions: no interactive effects of drug and expectation were observed at the neural level.…”
Section: B Additive Versus Interactive Effectsmentioning
confidence: 99%
“…One approach to investigate additive versus interactive effects of drug and placebo is to adopt a balanced placebo design (Rohsenow and Marlatt, 1981), in which the factors expectancy and drug alternate in a 2 Â 2 factorial manner. Employing just such a design, Atlas et al (2012) observed additive rather than interactive effects in conjunction with the influence of positive expectation on remifentanil analgesia. Their results were substantiated by a complementary fMRI study investigating pain-related responses during the open and hidden administration of varying remifentanil dosages, also allowing inferences about potential interactions: no interactive effects of drug and expectation were observed at the neural level.…”
Section: B Additive Versus Interactive Effectsmentioning
confidence: 99%
“…A recent study suggests that these two components operate independently from each other. Atlas et al (25) conducted a study to directly examine the relationship between expectations and opioid analgesia. They administered the opioid agonist remifentanil to human subjects during experimental thermal pain and manipulated participants' knowledge of drug delivery using an open-hidden design.…”
Section: B Therapeutic Rituals and Drugs: Common Pathways?mentioning
confidence: 99%
“…In a recent study (Atlas et al, 2012), a placebo manipulation was combined with a potent opiate, and participants' knowledge of drug delivery was manipulated in an open-hidden design. The opiate produced the most pronounced effects in the ACC, which was strongly associated with pain affect.…”
Section: Anticipation and Proactive Controlmentioning
confidence: 99%